Effects of language policy in South Africa with special reference to Tshivenda : exploring the interface between policy and practice - Murwamphida, Sedzani Caroline (My University, 2008)
This thesis endevours to examine the effectiveness of the implementation of the language policy of South Africa as enshrined in the Constitution of South Africa (1996) with special reference to Tshivenda. It is for this reason that an effort has been exerted to analyse the application of the aforementioned language policy pertaining to Tshivenda in areas such as social life, education and the business world. The study argues that as one of the eleven (11) official languages of South Africa Tshivenda deserves to be treated with the respect that it deserves. The study has clearly shown that Tshivenda is currently not fully enjoying the status that is accorded to it by the Constitution of South Africa (1996) because of multifold factors and reasons. One of these is that the business world does not derive much profit from the use of Tshivenda as it is seen as a minority language. In addition, the study has discovered that there are problems associated with translation as most of the time the translation is of a poor standard. It is thus crucial that translation must be conducted by people who have undergone professional training. Furthermore, a major stumbling block with regard to the use of Tshivenda in South Africa is the prevailing negative attitude that speakers of African languages harbour towards African languages in general. This does not come as a surprise as many African people still look down upon their languages as they are mostly regarded as backward and unsophisticated. This is why English is still dominant in many areas as people view it as a passport to green pastures. The study has indicated that the Constitution of South Africa (1996) clearly stipulates that all official languages should be used in all spheres of life where it is practicable. This implies, among others, the right of learners to be taught in their mother tongue. Although a large number of respondents are of the view that the use of English should not be tampered with, it is heartening to deduce that some people are now supporting the idea that Tshivenda should be used in all official communication. Finally, the study recommends the use of Tshivenda in social, educational and economic settings as this will indeed be a proof that Tshivenda-speaking people are also enjoying the fruits of the new democratic dispensation in South Africa.
Thesis (Ph.D. (Languages)) --University of Limpopo, 2008
Keywords: Language policy; Venda language; 306.44968; Language policy - South Africa; Venda language